IMPACT OF CANNABIS USE ON DEVELOPMENTAL MILESTONES IN YOUTH USERS - Dr. Aditi; Dr. Bibin C F; Dr. Ayushi Srivastava; Dr. Shekhar saini (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The impact of cannabis use on developmental milestones in youth users is a significant concern. cannabis use during adolescence can have lasting effects on cognitive function, brain development, and mental health.